THE INFLUENCE OF SERVANT LEADERSHIP AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE AT THE REGIONAL DISASTER MANAGEMENT AGENCY OF SERAM BAGIAN BARAT REGENCY THROUGH THE MEDIATION OF ORGANIZATIONAL COMMITMENT - Maria Crisnacecar Sikteubun; Conchita Valentina Latupapua; Agusthina Risambessy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the impact of servant leadership and emotional intelligence on employee performance at the Regional Disaster Management Agency of Seram Bagian Barat Regency, with organizational commitment as a mediating variable. Utilizing a quantitative approach, data were collected from 40 employees through a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares. The findings reveal that servant leadership has a significant direct effect on employee performance but does not significantly influence organizational commitment. Conversely, emotional intelligence demonstrates a strong positive effect on both organizational commitment and employee performance, indicating that emotionally intelligent employees exhibit higher commitment and better performance. Additionally, organizational commitment significantly mediates the relationship between emotional intelligence and employee performance, highlighting its essential role in translating emotional competencies into workplace effectiveness. However, organizational commitment does not mediate the effect of servant leadership on employee performance, suggesting that servant leadership enhances performance primarily through direct mechanisms rather than commitment-driven processes. These results emphasize the importance of developing employees’ emotional intelligence as a key strategy for improving both commitment and performance. The study contributes to leadership and organizational behavior research by providing empirical insights into the interplay between leadership style, emotional intelligence, and commitment in a high-stakes public sector environment. Future research should explore contextual factors such as organizational culture and job complexity to refine these findings further.